The Effect of Reward and Punishment on the Turnover Intention of Maharagung Organizer Crew - Rahmadani Farhansyah; Mei Retno Adiwati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research looks at why freelance event crews think about leaving Maharagung Organizer by focusing on two things: the rewards they receive and the punishments they face in a project-based setup. The core issue is that crews feel dissatisfied when rewards are unclear or rarely given, while discipline rules can feel uneven, so the goal is to see whether these practices actually change how much people want to quit. The study uses a simple survey design and analyzes the results with a PLS model in SmartPLS after checking that the questions reliably measure reward, punishment, and turnover intention, and it includes everyone active and reachable during the data phase. The results point one way: fair, transparent rewards help people want to stay, while discipline does more to set standards than to keep people from leaving; taken together, that means rewards carry most of the weight for retention, and punishments mostly support order and safety. The bottom line for managers is to make rewards predictable, tied to performance, and clearly communicated, then keep discipline fair and consistent in the background so crews feel respected and choose to keep taking future event offers.